Polyelectrolyte Complex Nanoparticles: Chitosan-Chondroitin Complex for Drug Delivery - Daníel Óskarsson 1999- (2024)
Polyelectrolyte complex nanoparticles (PEC) have emerged as promising vehicles for drug delivery due to their unique physicochemical properties and biocompatibility. This study investigated the formulation characteristics of PEC nanoparticles based on interpolymer ionic interaction between cationic chitosan derivative and anionic chondroitin sulfate. The objective was to optimize formulation parameters and assess the potential of PEC for drug delivery applications. The cationic derivatives were chitosan betaine (CB) and chitosan oligomer betaine (COS). The anionic components used for preparing the PECs were chondroitin sulfate (CS) polymer and sulfobutyl-ether-β-cyclodextrin (CD). The CB and COS were synthesized at the University of Iceland, while CS and CD were commercial products. CD was also used in the study because is a well-known excipient used as a solubilizer and stabilizer. CB had to be tested for solubility and all samples freeze-dried to confirm their concentrations. Once sample solutions of all the polymers had been prepared, PEC formulation studies were carried out with dynamic light scattering (DLS). Through systematic experimentation, DLS revealed optimal ratios for CB+CS, COS+CS, and these complexes with CD and indicated the successful formation of PEC in terms of size (size < 200 nm, polydispersity index < 0.2) Fluorescence resonance energy transfer (FRET) was employed using fluorescently labeled polymers. FRET verified that PEC was formed between the polymers and showed exciting results regarding CD potential to enhance PEC properties, suggesting a potential avenue for further research. TEM imaging then ultimately confirmed the formation of PEC. Cell uptake studies were then performed on individual polymers and PECs, which indicated that using PECs increased the cell uptake of the polymers compared to polymers used on their own. Cytotoxicity test confirmed that only CB was cytotoxic and that the PEC reduced this toxicity. Overall, the findings suggest that these PECs hold significant ...